Peningkatan Kesadaran Berbangsa dan Bernegara pada Siswa di SMP Santo Paulus Abepura - Muhammad Khaidir Kahfi Natsir; Dwight Nusawakan; Annisa Fitriah Mudassir; Abdul Malik Mufty (Lembaga Pengembangan Kinerja Dosen, 2025)
Technological advances that occur in the Globalization Era have a major impact on a person's mental development, especially for High School Students who in their daily activities require updated information to develop their abilities. The activities carried out if not accompanied by an understanding of the dynamics of social change, they will experience problems of Moral Decadence due to the lack of understanding of National and State Awareness. One form that can be done to increase students' understanding of the importance of national and state awareness is through counseling activities. Therefore, the provision of material on understanding the Increase in National and State Awareness to the young generation of Indonesia must always be carried out with the aim that the young generation of Indonesia can understand the positive culture in Indonesia which is very important to implement in order to create unity and unity of the Indonesian nation.